Rammens udkrængning: Om Sasha Waltz’ teaterinstallation Insideout (2003) - Thygesen, Mads (Peripeti, 2024)
In his analysis of German choreographer Sasha Waltz’ dance performance Insideout, Mads Thygesen explores the relations between the intentions of the work and its actual, performative »doing«, specifically the way this performance draws attention to its own use of framing devices in the interaction with the audience.